Pelatihan Memperbaiki Peralatan Listrik Rumah Tangga Pada Masyarakat Di Pare Pare Sulawesi Selatan - Wahrini, Retyana Wahrini; Hasbi (Cattleya Darmaya Fortuna, 2023)
This community service activity was carried out for the people of Pare Pare South Sulawesi. This service activity is carried out in the form of training in the maintenance and repair of household electrical appliances. The purpose of this community service activity is to provide community service by providing training on: how to maintain household electrical appliances in general, diagnose damage, and repair damage based on diagnosis. Materials provided in this training include: maintenance of household electrical appliances, repair of damage to household electrical appliances, operation of household electrical appliances, and installation of household electrical devices. The implementation of community service regarding household electrical appliances ran smoothly. This community service activity has yielded results; increasing participants' knowledge of the benefits of maintaining electrical appliances, increasing participants' knowledge of damage diagnosis, and increasing participants' knowledge of correct repairs of household electrical appliances